Peran dan Dampak Sosial Panti Asuhan Bumi Keselamatan Margarita di Kabupaten Simalungun Tahun 2015-2021 - Sihombing, Imam Daniel; Tarigan, Prisai Mono Putra; Sipangkar, Romarta Christina; Wardina, Siti; Febrianto, Erlangga Bagus; Cahyani, Ririn Dwi; Purba, Ridwin (Samsara Institute Publisher, 2025)
Bumi Keselamatan Margarita Orphanage is one of the orphanages located in . Like other orphanages, the orphanage, abbreviated as BKM, has a significant social impact in Simalungun Regency. One of its impacts is providing a meaningful life for children, nurturing their spirituality, and offering the best education for the residents of the orphanage. The aim of this research is to enrich the historiography of the role of orphanages and churches in empowering the surrounding communities, so that the historical narrative about orphanages becomes more complete and enhances the image of orphanages as institutions that also liberate people. The method used is the historical method, which consists of heuristics, criticism or verification, interpretation, and finally historiography. The results show that Bumi Keselamatan Margarita Orphanage has had a considerable impact around the Simalungun Regency, which are its main areas. They have done many things, such as providing shelter for children from early childhood to teenagers, empowering children by offering education and preparing them for industrial skills, and providing scholarships to those in need. As a result, this orphanage still remains a reliable place for abandoned children to receive proper care when their parents are no longer around, helping them strengthen one another and grow their spiritually, so they can become kind and character-driven individuals in the future, even though the figure of their mother and father is no longer present to their lives.